Effect of Ti additions on mechanical properties of NbMoTaW and VNbMoTaW refractory high entropy alloys. (May 2017) - Han, Z.D.; Chen, N.; Zhao, S.F.; Fan, L.W.; Yang, G.N.; Shao, Y.; Yao, K.F.
Abstract: With Ti addition in a NbMoTaW alloy, a new refractory high entropy alloy (HEA) of TiNbMoTaW was developed. It has been found that this HEA possesses single body-centered cubic (BCC) phase structure, and could sustain the phase structure even after annealing at 1200 °C for 24 h. In comparison with the mechanical properties of the NbMoTaW and VNbMoTaW HEAs, the room-temperature yield strengths and compressive plastic strains of the TiNbMoTaW and TiVNbMoTaW HEAs are significantly enhanced. In particular, the TiNbMoTaW and TiVNbMoTaW HEAs also show very promising high temperature strength. Their yield strengths are as high as ∼586 and ∼659 MPa at 1200 °C, respectively. The present results indicate that Ti addition is beneficial to the strength and the compressive ductility of the refractory HEAs at room-temperature. It is suggested that the present refractory HEAs possess the potentials in applications of high temperature structure materials. Highlights: The NbMoTaW and VNbMoTaW HEAs possess outstanding mechanical properties at high temperature, while they are brittle at room-temperature, which would limit their broad applications. In the present work, we successfully improve their strengths and the compressive ductility at room-temperature by the alloying method. It is found that element segregation may contribute to the ductility of the HEAs. The high-temperature mechanical performance of the TiNbMoTaW and TiVNbMoTaW HEAs makes them to be potential materials for high-temperature applications.